O(3P) atoms as a chemical probe of surface ordering in ionic liquids - Waring, C; Bagot, P; Slattery, J; Costen, M; McKendrick, K (2010)
The reactivity of photolytically generated, gas-phase, ground-state atomic oxygen, O(3P), with the surfaces of a series of 1-alkyl-3- methylimidazolium bis(trifluoromethylsulfonyl)imide ([NTf2]) ionic liquids has been investigated. The liquids differ only in the length of the linear CnH2n+1 alkyl side chain on the cation, with n = 2, 4, 5, 8, and 12. Laser-induced fluorescence was used to detect gas-phase OH v′ = 0 radicals formed at the gas-liquid interface. The reactivity of the ionic liquids increases nonlinearly with n, in a way that cannot simply be explained by stoichiometry. We infer that the alkyl chains must be preferentially exposed at the interface to a degree that is dependent on chain length. A relatively sharp onset of surface segregation is apparent in the region of n = 4. The surface specificity of the method is confirmed through the nonthermal characteristics of both the translational and rotational distributions of the OH v′ = 0. These reveal that the dynamics are dominated by a direct, impulsive scattering mechanism at the outer layers of the liquid. The OH v′ = 0 yield is effectively independent of the bulk temperature of the longest-chain ionic liquid in the range 298-343 K, also consistent with a predominantly direct mechanism. These product attributes are broadly similar to those of the benchmark pure hydrocarbon liquid, squalane, but a more detailed analysis suggests that the interface may be microscopically smoother for the ionic liquids. © 2010 American Chemical Society.